The Effectiveness of a High-Protein Liquid Dietary Supplementation in Improving Nutritional Status of Malnourished Patients in Hospital Care: a Preliminary Study - Simadibrata, Marcellus; Abdullah, Murdani; Witjaksono, Fiastuti; Muzellina, Virly Nanda; Utari, Amanda Pitarini; Wulandari, Yohannessa; Wijayanti, Ari; Mustikarani, Dewi; Haloho, Raja Mangatur; Rachman, Aditya; Simadibrata, Daniel Martin; Mutiara, Rizka; Renaldi, Kaka (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Malnutrition is a very common problem in hospitalized patients. Based on studies conducted in various countries, the prevalence of hospital malnutrition ranges from 20-45%. Hospital malnutrition can occur as a result of insufficient nutrient intake, impaired absorption of nutrients in the gastrointestinal (GI) tract, loss of nutrients due to disease, or increased metabolic requirement during illness. Nutrition is the basis for the healing process as it requires good nutrients through various enzymatic reactions. Some studies have shown that hospital malnutrition increases morbidity, mortality, prolongs the duration of hospitalization, and delays recovery. To improve nutritional status, a high-protein diet can be given. Liquid diet is one of the alternative forms of nutrition because it is easier to swallow.Method: This study was a double-blind randomized controlled trial conducted to assess the effectiveness of high protein liquid dietary supplementation in malnourished hospitalized patients. The patients were assessed for their nutritional status based on ESPEN 2015 criteria. Patients who experienced malnutrition will be divided into 2 groups, namely the control group which was given normal protein liquid diet, while the intervention group was given high protein liquid diet supplementation as much as 2 bottles (200 mL) per day for 7-10 days. Furthermore, the nutritional status of the patient was assessed.Results: By administering high-protein liquid diet supplementation, there was a tendency to increase the strength of the right handgrip in 3 subjects (50%), the tendency to increase body mass index (BMI) in 3 subjects (50%), Subjective Global Assessment (SGA) score improved in 2 subjects with mild/moderate malnutrition (33.3%) and 1 subject with normal nutrition (16.7%), and the tendency to increase the fat-free mass in 3 subjects (50%).Conclusion: The administration of high protein liquid dietary supplementation tended to increase the strength of the right handgrip, BMI, SGA score, and body fat-free mass index.